Decoding Dishevelled-Mediated Wnt Signaling in Vertebrate Early Development - Shi, De-Li (Frontiers in Cell and Developmental Biology, 2020)
Dishevelled proteins are key players of Wnt signaling pathways. They transduce Wnt signals and perform cellular functions through distinct conserved domains. Due to the presence of multiple paralogs, the abundant accumulation of maternal transcripts, and the activation of distinct Wnt pathways, their regulatory roles during vertebrate early development and the mechanism by which they dictate the pathway specificity have been enigmatic and attracted much attention in the past decades. Extensive studies in different animal models have provided significant insights into the structure-function relationship of conserved Dishevelled domains in Wnt signaling and the implications of Dishevelled isoforms in early developmental processes. Notably, intra- and inter-molecular interactions and Dishevelled dosage may be important in modulating the specificity of Wnt signaling. There are also distinct and redundant functions among Dishevelled isoforms in development and disease, which may result from differential spatiotemporal expression patterns and biochemical properties and post-translational modifications. This review presents the advances and perspectives in understanding Dishevelled-mediated Wnt signaling during gastrulation and neurulation in vertebrate early embryos.